MANNER ADJUNCT IN ENGLISH AND THE IMPLICATION IN THE TEACHING OF EFL - Ni Luh Ketut Mas Indrawati (Universitas Negeri Padang, 2015)
This paper aims at analyzing the forms and position of the English manner adjunct and the implication in the teaching of English grammar in EFL. Manner adjunct in a sentence should how the activity or event stated in the verb is performed. This study applied descriptive qualitative method and the data were collected through library research. The data rvere taken fiom the novels 'Knife of Dreams' and'The Lord of the Rings'. The theory adopted in this study u,as the theory ofmanner adjunct proposed by Quirk et al (1985) and the theory, of communicative language teaching by Harmer (1983). Quirk et al (1985) mentions that the English manner adjunct can be in the form of an adverb of manner (i.e.: quickly. slowly) prepositional phrase (i.e.: in a different way), and clause (i.e.: as I tell you). Meanrvhile the position of the adverbial of manner can take initial. middie, and end position. The findings shou' that Adverbial of manner could be in the form of prepositional phrase and clause in terms of positions; they are found in the initial, medial and end position. This implies that in the teaching of manner adjunct in EFL should be directed to students' communicative efficiency which is apply to student at different levels. grammar. situational and context, pronunciation and accent and skills.